Islamic elementary school quality improvement in capital theory perspective - Baharudin Baharudin; Yoyon Suryono; Sugito Sugito; Habibi Habibi; Ida Fiteriani (International Journal of Evaluation and Research in Education (IJERE), 2022)
Improving the quality of Islamic schools in the midst of advances in industrial technology 4.0 is an obligation in education world. This research aimed to explore comprehensive information in order to describe the trends and Islamic elementary schools’ strategies in making changes through capital theory approach for quality improvement in a new perspective in the globalization era. The capital theories aspects are: intellectual, social, spiritual, and financial as an analytical framework to find out how schools are transformed. Three Islamic elementary schools with type of A, B and C criteria have been involved. A qualitative approach has been used and the findings are described according to Milles and Haberman's clausal network model. Data was collected through interviews, observation and documentation. The research found that the strategy used by each Islamic elementary school in improving quality were different and strongly influenced by the leader in developing and utilizing the capital existence according to the situation. It can be seen that there is a dominance of one capital aspect that is used to facilitate the other. This presentation is based on the perspective of capital theory in the Indonesian context. In the future, it can be used as a basis for conducting further research in carrying out school transformation more broadly.